2016
DOI: 10.3390/nu8020084
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Presence of Non-Celiac Gluten Sensitivity in Patients with Functional Gastrointestinal Symptoms: Results from a Multicenter Randomized Double-Blind Placebo-Controlled Gluten Challenge

Abstract: Non-celiac gluten sensitivity (NCGS) is characterized by the onset of symptoms after eating gluten-containing food. We aimed to single out NCGS subjects among subjects with functional gastrointestinal symptoms. Patients were enrolled in a multicenter double-blind placebo-controlled trial with crossover. Symptoms and quality of life were evaluated by means of 10-cm VAS and SF36. Iron parameters, transaminases and C reactive protein (CRP) were evaluated. After a three-week-long gluten-free diet (GFD), responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(183 citation statements)
references
References 25 publications
10
167
0
6
Order By: Relevance
“…[8] Our data confirm the ethiopathogenetic role of immune response in MD, in agreement with other recent observations. [25,26,27] and our previous observation of a gluten immune reactivity in MD patients. [17,18] The association between NCGS and MD should be supported by dietary exclusions and challenges: symptoms improve or disappear upon gluten withdrawal, while they recur if gluten is reintroduced in the diet.…”
Section: Discussionsupporting
confidence: 74%
“…[8] Our data confirm the ethiopathogenetic role of immune response in MD, in agreement with other recent observations. [25,26,27] and our previous observation of a gluten immune reactivity in MD patients. [17,18] The association between NCGS and MD should be supported by dietary exclusions and challenges: symptoms improve or disappear upon gluten withdrawal, while they recur if gluten is reintroduced in the diet.…”
Section: Discussionsupporting
confidence: 74%
“…Some IBS and FD patients, without evidence for celiac disease based on serological markers and histology, experience substantial improvement in symptoms upon withdrawal of gluten from their diet. In a multi-center double-blind placebo-controlled trial, 140 patients with functional GI symptoms were randomized to a strict 3-week gluten-free diet (GFD) [22]. Responders to GFD were asked to continue with the diet, but were re-challenged with gluten or placebo in a double-blind manner.…”
Section: The Role Of Dietmentioning
confidence: 99%
“…45 Although unselected IBS patients display clinical improvement after wheat withdrawal, only a proportion may truly reflect underlying gluten sensitivity (Table 1). [46][47][48][49][50][51][52][53][54][55][56] The absence of specific biomarkers and the great proportion of patients with placebo effect observed in IBS trials, are 2 barriers for identifying the specific role of wheat components in generating IBS symptoms. Therefore, double-blind-placebo-controlled-crossover (DBPCC) trials are a reliable way to establish whether wheat and its fractions are involved in IBS symptom induction.…”
Section: Dietary Factors In Irritable Bowel Syndromementioning
confidence: 99%
“…48 In a second trial from the same group, 51 IBS patients that responded to a gluten-free diet were challenged with low dose of gluten (2 g/day), high dose of gluten (16 g 54 The results showed that pure gluten ingestion induced recurrence of a variety of symptoms including, bloating, abdominal pain, foggy mind, aphthous stomatitis, headache and depression, but not in all of NCGS patients. Two recent DBPCC trials 55,56 performed in IBS patients self-diagnosed as "gluten/wheat sensitive" strongly suggested that gluten/wheat was responsible for symptom generation in up to one-third of IBS patients. Overall the results indicated that gluten and other wheat proteins cause symptoms in the absence of celiac disease in a subset of the IBS population ( Table 2).…”
mentioning
confidence: 99%